Assessing The Effectiveness of Media in Promoting Community Health in Lusaka, Zambia: A Case Study of Reproductive Health in Lusaka - Bridget Banda; Kabubi Marvin (International Journal of Advanced Multidisciplinary Research and Studies, 2026)
This study examines the significant role of media in promoting community health initiatives, focusing on the experiences and perspectives of health workers in Lusaka, Zambia. It investigates the use of traditional media, such as radio and television, alongside digital platforms in disseminating crucial health information to address persistent challenges, including infectious diseases, malnutrition, and the rising prevalence of non-communicable diseases. The research critically evaluates the effectiveness of media-driven health promotion strategies, emphasizing key factors such as audience engagement, cultural relevance, and message clarity. Health workers, serving as vital intermediaries between media campaigns and the communities they aim to reach, are pivotal in translating health messages into practical actions that improve public health outcomes. The study highlights the strengths and weaknesses of existing media approaches, noting the broad reach and accessibility of media platforms but also identifying gaps such as insufficient audience targeting and limited cultural sensitivity. By assessing the impact of these strategies on health-related behaviours, the research outlines opportunities for improving public health communication frameworks. The findings emphasize the importance of culturally tailored and inclusive messaging and underscore the need for empowering health workers with the tools and resources necessary for effective community engagement. Ultimately, the study offers valuable insights for designing more impactful and culturally resonant health promotion strategies, with implications not only for Lusaka but also for similar urban contexts worldwide, where media can play a transformative role in addressing complex health challenges.